Prevalence of diarrheagenic Escherichia coli and impact on child health in Cap-Haitien, Haiti. - Jenna N Diaz; Lora L Iannotti; Sherlie Jean Louis Dulience; Sydney Vie; Xuntian Jiang; Vadim Grigura; Jacques Boncy; Francesca J Marhône Pierre; F Matthew Kuhlmann (PLOS Global Public Health, 2023)
Background Diarrheagenic Escherichia coli (DEC) are common pathogens infecting children during their growth and development. Determining the epidemiology and the impact of DEC on child anthropometric measures informs prioritization of prevention efforts. These relationships were evaluated in a novel setting, Cap-Haitien, Haiti. Methods We performed pre-specified secondary analysis of a case-control study of community-dwelling children, 6-36 months of age, enrolled 96 cases with diarrhea and 99 asymptomatic controls. Assessments were performed at enrollment and one month later at follow-up. Established endpoint PCR methodologies targeted DEC gDNA isolated from fecal swabs. The association between DEC and anthropometric z-scores at enrollment was determined using multivariate linear regression. Lastly, we assessed the association between specific biomarkers, choline and docosahexaenoic acid (DHA) and diarrheal burden. Results Enterotoxigenic Escherichia coli (ETEC) was identified in 21.9% of cases vs. 16.1% of controls with heat-stable producing ETEC significantly associated with symptomatic disease. Enteroaggregative E. coli (EAEC) was found in 30.2% of cases vs. 27.3% of controls, and typical enteropathogenic E. coli in 6.3% vs. 4.0% of cases and controls, respectively. Multivariate linear regression, controlled for case or control status, demonstrated ETEC and EAEC were significantly associated with reduced weight-age z-score (WAZ) and height-age z-score (HAZ) after adjusting for confounders. An interaction between ETEC and EAEC was observed. Choline and DHA were not associated with diarrheal burden. Conclusions DEC are prevalent in north Haitian children. ETEC, EAEC, household environment, and diet are associated with unfavorable anthropometric measures, with possible synergistic interactions between ETEC and EAEC. Further studies with longer follow up may quantify the contribution of individual pathogens to adverse health outcomes.